Study on Very Fast Transient Overvoltage Characteristics of Gas-Insulated Switchgear Substation Based on Hybrid Reactive Power Compensation. (29th September 2022) - Wen, Caiquan; Yang, Zheng; Lu, Yitao; Huang, Yongfeng; Lin, Hanliang; Zhang, Zhiyuan; Chen, Taiyu; Liu, Yingnan
Abstract : In recent years, gas-insulated switchgear (GIS) substations have become widely used in power systems. Due to their compact structure, extremely high oscillation frequencies are prone to extremely high oscillation transient overvoltages or very fast transient overvoltages (VFTOs) when the isolating switch or circuit breaker is operated. The characteristics of these special fast transient processes in GIS and the effect of hybrid reactive power compensation (HRPC) on these fast transient processes were studied. A simulation of the GIS model was established, and based on the transient model of HRPC and the theory of the transmission line, the effects of VFTO produced by HRPC switching operation and the parameters of HRPC on VFTO were studied and the differences in the characteristics of VFTOs in substations with or without HRPC. Based on the conclusions of our study on the influence of HRPC on VFTO, the inhibitory effects of a ferrite magnet ring and an inhibitor busbar on VFTO were verified.